ADAPTASI DAN PERUBAHAN PERILAKU SISWA LAKI-LAKI DAN PEREMPUAN DI LINGKUNGAN SEKOLAH MENENGAH KEJURUAN NEGERI 4 DAN NEGERI 5 AMBONâ€ - Cost Sahanaya; Costansa Glory Lessil; Anthonio Johan Latuihamallo; Jospater Proim (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Vocational High School 4 ( SMK ) and Vocational High School 5 is intitution of education which indeep social proccec named social relationship, this relations by sociology called interaction. Social interaction is one of factor to happening social activity and presence social fact based on individu motivation and social actions. More activity to both of that school happened because some factor like ; 1. Imitation, 2.Suggestion, 3.Indentification, 4.Sympatic, and 5. Motivation. In interaction factor we can see ‘whole life’ which collect value internalization and socialitation between all component in school among boys and girls. In this summary writter can see adaptation between boys and girls in school, it means between some of boys dominate enviroment of school how can girls adaptation theirself and the other hand if girls dominate enviroment of school how can boys adaptation. Woman by socialization in their life as balancer of powerman. Woman have not same experience to handle some enviroment which free from intervention of other people especially ( man ), and the other hand experience of man is not free from intervention of other people ( woman ) in some space, as theory ‘subjectif or united relize.